UEWDM user interface design: a case study of i-GIMS - Mubin, Siti Azreena; Jantan, Azrul Hazri; Abdullah, Rusli; Kamaruddin, Azrina (American Scientific Publishers, 2018)
Web applications have a different complex features and it raised new issues in design modeling, including user interface design in web application development. The design phase should be able to cope with those user interface modeling issues such as lack of GUI aspects and web designers should provide a clear design view in the web design process. Thus, in this paper, we propose sub-design models in UEWDM user interface design phase by separating it into two sub-designs called Logical Abstract Model and Physical Abstract Model. Our contributions rely on the user interface design structure pattern, which would be able to support the complex processes modeling in GUI aspects. The proposed approach is demonstrated through i-GIMS UPM case-study, a portal for postgraduate student.